GAMBARAN PERAN KELUARGA DALAM PEMENUHAN ACTIVITY DAILY LIVING (ADL) LANSIA PASCA STROKE DI DESA GUNUNGRONGGO KECAMATAN TAJINAN - Nanda Eka Retnani; Lenni Saragih; Zainol Rachman (Politeknik Kesehatan Kemenkes Malang, 2020)
Abstract:The role the family must play in order to fulfill the expectations of themselves or others in the family. The elderly during post-stroke are in a critical phase of recovery. The purpose of this study was to describe the role of the family in meeting the daily needs of the post-stroke elderly.. The purpose of this study was to describe the role of families in fulfilling ADL in post-stroke elderly. The design of this study is a descriptive case study. This study used two family subjects who had family members suffering from post-stroke. This research was conducted on 7-12 January 2019. This research method was interview and observation. The results of the case studies obtained were that both subjects carried out their roles as motivators and family nurses. The conclusion of this study is that both families play a good role by obtaining a score of 43 and 39. Recommendations for future researchers are expected to conduct similar research, but examine other types of informal roles so that other actions can be taken by the family in fulfilling the ADL of post-stroke elderly.